Autopsy-certified maternal mortality at Ile-Ife, Nigeria - Dinyain, Amatare (Dove Medical Press, 2013)
AIM: Maternal mortality is a major health problem, especially in Nigeria, where accurate autopsy-based data on the prevalent causes are not readily available. The aim of this study was therefore to accurately determine the causes of maternal death as seen in a tertiary health facility in Nigeria. MATERIALS AND METHODS: This was a descriptive, retrospective review of the postmortem autopsy findings from cases of maternal death at the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria over a 5-year period. Analyses were performed for differences in proportions using PEPI computer programs for epidemiologists (P is significant at <0.05). RESULTS: A total of 84 cases of maternal deaths were used for the study. Approximately 71.4% of the maternal deaths were due to direct causes and 28.6% were due to indirect causes. The mean age at the time of death was 27.9±7.5 years. Overall, the three leading causes of death were obstetric hemorrhage (30.9%), complications of abortion (23.8%), and nongenital (nonobstetric) infections (14.2%). Of the direct causes of maternal death, obstetric hemorrhage (43.3%) was the leading cause, with postpartum hemorrhage accounting for most (65.0%) of such deaths; other causes included complications of unsafe induced abortion (33.3%) and of labor (11.7%). Of the indirect causes, nongenital infections (50.0%), anemia (25.0%), and preexisting hypertension (20.8%) accounted for the majority of the maternal deaths. There was disparity between the clinical and autopsy diagnoses in 34 of the 84 cases (38.1%). CONCLUSION: The leading causes of maternal death in this study are similar to those in other developing countries. Autopsy is an invaluable tool in accurately determining the cause of maternal death.